O sujeito da techne – O problema do desenho da vivência da justiça - Rui Artistides Lebre (e-cadernos ces)
Understanding the democratization of justice as a political problem, we propose to interpret the discipline and practice of architecture as a political reflection. The organization of space does not by itself produce social and political changes; however, it cannot be exempted from its role in the production of life settings. This is the condition we wish to discuss. We will try to identify those dispositions that define an intimacy between architecture and politics, with the goal of delineating a field of design, endogenous to architecture, in which the possibility of shape is taken as the objective and subjective managing of bodies. This argument will depart from a discussion of the concept of techne and its implications for the art of building. It will furthermore allow to sketch an experimental work hypothesis in which the question of a possible democratization of justice may be imagined through spatial practices.